BUDAYA HARI JUMAT SEBAGAI SARANA PENDIDIKAN KARAKTER DI SMK NEGERI 6 SURAKARTA - Anggita Ratih Lidiatanti; Sumardi Sumardi (Buletin Literasi Budaya Sekolah, 2023)
The low character of the younger generation is one of the problems faced by education in Indonesia. This study aims to explain the concept of Friday school culture and the characters that can be formed through Friday school culture. Friday school culture contains values that can be used as a means to shape the character of students. This study uses a qualitative descriptive research method. Data were obtained through interviews with the vice principal of student affairs II, teachers, and students at SMK Negeri 6 Surakarta. The results of this study indicate that the culture of the Blessed Friday school contains religious values, nationalism, creativity and mutual cooperation which can be internalized to students as an effort to shape and improve character. The characters that can be formed through the Friday Blessings school culture are tough, clean and healthy characters, disciplined, caring for the environment, teamwork, responsibility, creative and innovative.